(untitled) (International Seven Journal of Health Research, 2025)
Conscious sedation is widely used in contemporary dentistry to manage anxiety and fear, ensuring greater comfort and safety during clinical care. This study aims to review recent literature on the clinical and pharmacological perspectives of conscious sedation, with an emphasis on pharmacological agents, routes of administration, indications, and safety protocols. This integrative review was conducted in the PubMed, SciELO, and BVS databases, covering publications published between 2020 and 2025. The results show that nitrous oxide and midazolam remain the most commonly used drugs, standing out for their efficacy and safety profile when administered by qualified professionals. Technological and pharmacological advances have allowed greater control of sedation levels and reduced adverse effects, consolidating conscious sedation as an essential resource in modern dental practice.